1997
DOI: 10.1007/bf02488967
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional changes after portal vein occlusion in rats

Abstract: We studied the morphological and functional changes after ligation or embolization of a portal vein branch that perfused the median and the left lateral lobes of the liver in rats. After surgery, regenerative hypertrophy in the non-occluded liver lobes and atrophy in the occluded liver lobes were seen. In the non-occluded liver lobes, mitosis of the hepatocytes was seen most frequently on postoperative day 2. The density of the Kupffer cells after postoperative day 2 was about twice that in intact rats. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…This mass loss was fully compensated by the rapid weight gain observable in case of the PVNL lobes; consequently, the total liver weight remained constant. The weight gain in PVNL lobes reached a plateau phase between the fifth and seventh days at approximately 329% of the baseline, which finding was consistent with previously published data [5,21,22]. However, the specific alterations in hepatic lobar structure have not been assessed so far.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This mass loss was fully compensated by the rapid weight gain observable in case of the PVNL lobes; consequently, the total liver weight remained constant. The weight gain in PVNL lobes reached a plateau phase between the fifth and seventh days at approximately 329% of the baseline, which finding was consistent with previously published data [5,21,22]. However, the specific alterations in hepatic lobar structure have not been assessed so far.…”
Section: Discussionsupporting
confidence: 89%
“…On the seventh day, the liver lobules of the PVL lobes became considerably smaller and were characterized by contracted portal triads and narrowed sinusoids. Earlier, Tanaka et al [21] and Yamasaki et al [33] demonstrated that arterialization of the PVL lobes (absence of portal nutrients, hormones, and other mediators) led to the partial capillarization of liver sinusoids, characterized by a decreased number of fenestrae and porosity, as well as by partial development of the basement membrane. These alterations can reduce the diffusion of protein-bound substances such as ICG and are most likely responsible for the permanent functional impairment observed by us in the PVL lobes.…”
Section: Discussionmentioning
confidence: 98%
“…However, the lobules have become smaller (the portal areas lie closer to each other). At the edge of the shrunken lobules, contracted portal triads can be found together with a fibrotic thickened portal vein, a collapsed bile duct and an enlarged hepatic artery [39,40]. Furthermore, the sinusoidal spaces are narrowed, and the number of fenestrations per endothelial cell decreases with the partial formation of basement membrane [41].…”
Section: Atrophymentioning
confidence: 99%
“…According to the most widely used laboratory blood tests (prothrombin time and antithrombin III, albumin, bilirubin and transaminase levels), liver function remains stable after PVO [40,64,67]. However, the blood concentration of liver-related biochemical substances is dependent on many factors (blood flow, volume of distribution, availability or elimination).…”
Section: Functional Regeneration - Other Than Volume Shiftingmentioning
confidence: 99%
See 1 more Smart Citation